Using Reflexive, Introspective and Storytelling Tools: Towards Becoming More Autoethnographic in Academia - Manuel Au- (MDPI AG, 2020)
The aim of this article is to show how autoethnography is a useful and revealing research methodology that should be encouraged in academia, especially in higher education. With objectivity, autoethnography, which is a relatively new approach, may be a path toward deeper cultural discussions that are so important in everyday life. Moreover, autoethnography leads to important reflexive and critical observations made by students. Autoethnography is a readily accessible, low-cost methodology and thus very appealing to students and younger researchers. With this article, the author exemplifies autoethnographic accounts and narrates three different stories that occurred while trekking with three different trekking guides in Patagonia (El Chaltén), Argentina. Argentinian culture, in South America, is the focus. Researchers need to be careful of misleading statements in the literature, such as that in Argentina modesty is apparently not tolerated. We found that two of our guides and leaders - Mariano and Liz - both had modest (and pleasant) demeanors. Hence, we conclude that it is important to maintain an open mind and resist categorizing people. This is a vital point of cultural studies that is often not taken seriously. Cultures are made up of individuals and thus many differences can be found in the midst of an attempted standardization, and the desire to put everyone in the same "basket".